Prevalência de asma e rinite em escolares expostos às emissões da queima de cana de açúcar - Riguera, Denise (2010)
Respiratory diseases are the second most frequent cause of hospitalization by the Brazilian Unified Health System (SUS). SUS is responsible for 1,541,113 admissions throughout the country. Asthma and Rhinitis are considered the most common chronic diseases among children and teenagers. Their prevalence has been significantly increased becoming a major public health problem. There is a wide range variation in prevalence of reported asthma, rhinitis, and their symptoms. The observed differences can be, at least in part, due to methodological problems in defining asthma symptoms. The International Study of Asthma and Allergies in Childhood (ISAAC) was developed in an attempt to standardize the methods used in epidemiological studies. It is used to evaluate and compare the prevalence and severity of asthma, rhinitis, and eczema among different cities and countries. In Brazil, the standardized ISAAC questionnaire was translated and validated. Several studies pinpoint that social and environmental factors such as the Western lifestyle, urbanization, and increased population density can be considered as important determinants in the prevalence of asthma and rhinitis. Air pollution has also been identified as an exacerbating factor of these allergic diseases. More recent studies have shown the association between air pollution due to cane trash burning and respiratory morbidity, thus increasing the amount of daily inhalation at the Emergency Service and hospitalizations due to respiratory problems. Objective: To estimate prevalence of asthma, rhinitis, related respiratory symptoms, and predisposing factors in students from Monte Aprazível, São Paulo State, and to evaluate the role of daily exposition to air pollution on respiratory function of these students. Monte Aprazível is a low-population density city, with low motor traffic; warm climate; and a predominantly sugarcane-based agriculture. Casuistry and Method: This is a descriptive transversal study in children ranging from 10-14 years of age, using a questionnaire composed of asthma and rhinitis components of ISAAC protocol, along with socio-demographic and predisposing factor questions, family and personal past medical history. Repeated measures of peak expiratory flow in children, and black carbon and PM2,5 concentration levels were carried out. Results: Prevalence of asthma and rhinitis was 11% and 33.2%, respectively. From the asthmatic children, 10.4% presented four or more wheezing attacks in the past 12 months. Past family history was associated to presence of current asthma and rhinitis. Regarding rhinitis, there was also an association with presence of mold and cracks on the house. Rhinitis was most frequent from June to October, which matches sugarcane harvest season. Daily prevalence of PEF beneath 80% of the median was higher in days with greater concentration of PM2,5. Conclusion: Prevalence of asthma is below national average and that of rhinitis is above. Evidence suggests that pollution levels in cane trash burn season, although within acceptable levels, can be contributing to exacerbation of asthma and rhinitis episodes.